Driving green technology innovation: The impact of environmental policies on manufacturing - Wensheng Wang; Xi Yang (Journal of Innovation & Knowledge (JIK), 2025)
Environmental regulations have been extensively studied in the context of advocating green development. As one of the most stringent laws in history, the new Environmental Protection Law (EPL) of 2015 has greatly affected the production and development of enterprises. In this context, and in the face of the incentive problem of green technology innovation, what impact does this legislation have on the quantity and quality of green technology innovation activities of manufacturing enterprises? This study takes the new EPL as a representative policy of environmental regulation, and the A-share listed companies from 2010 to 2022 as a sample, and uses the differences-in-differences model to explore the impact of environmental regulation policies on green technology innovation. The results show that although the implementation of the new environmental protection law has enabled an expansion of the quantity of green technology innovation, it has also led to a decline in the quality of related innovation activities. It also finds differences based on the nature of enterprise property rights, with the quantity and quality of green technology innovation of state-owned enterprises being significantly higher than that of non-state-owned enterprises. Differences based on enterprise scale are also noted; compared with small-scale enterprises, the number of green technology innovations of large-scale enterprises is higher under the new environmental protection law, while the quality is not significantly different. The conclusions of this study provide theoretical support and counter-measures for deepening the reform of environmental regulation-related systems and formulating differentiated policy support measures for enterprises with different ownership types and scales.
Keywords: O31; O38; Q58; 650; Environmental regulation; Environmental protection law; Green technology innovation; Differences-in-differences model; Manufacturing enterprises